Effectiveness and cost-utility of a guided self-help exercise program for patients treated with total laryngectomy: protocol of a multi-center randomized controlled trial. Issue 1 (December 2016) - Jansen, Femke; Cnossen, Ingrid; Eerenstein, Simone; Coupé, Veerle; Witte, Birgit; van Uden-Kraan, Cornelia; Doornaert, Patricia; Braunius, Weibel; De Bree, Remco; Hardillo, José; Honings, Jimmie; Halmos, György; et al.
Abstract Background Total laryngectomy with or without adjuvant (chemo)radiation often induces speech, swallowing and neck and shoulder problems. Speech, swallowing and shoulder exercises may prevent or diminish these problems. The aim of the present paper is to describe the study, which is designed to investigate the effectiveness and cost-utility of a guided self-help exercise program built into the application "In Tune without Cords" among patients treated with total laryngectomy. Methods/design Patients, up to 5 years earlier treated with total laryngectomy with or without (chemo)radiation will be recruited for participation in this study. Patients willing to participate will be randomized to the intervention or control group (1:1). Patients in the intervention group will be provided access to a guided self-help exercise program and a self-care education program built into the application "In Tune without Cords". Patients in the control group will only be provided access to the self-care education program. The primary outcome is the difference in swallowing quality (SWAL-QOL) between the intervention and control group. Secondary outcome measures address speech problems (SHI), shoulder disability (SDQ), quality of life (EORTC QLQ-C30, QLQ-H&N35 and EQ-5D), direct and indirect costs (adjusted iMCQ and iPCQ measures) and self-management (PAM). Patients will be asked to complete these outcome measures at baseline, immediately after the intervention or control period (i.e. at 3 months follow-up) and at 6 months follow-up. Discussion This randomized controlled trial will provide knowledge on the effectiveness of a guided self-help exercise program for patients treated with total laryngectomy. In addition, information on the value for money of such an exercise program will be provided. If this guided self-help program is (cost)effective for patients treated with total laryngectomy, the next step will be to implement this exercise program in current clinical practice. Trial registration NTR5255 Protocol version 4 date September 2015.